Using the Valeo dilatable stent in coarctation stenting for small children: expanding the inclusion criteria for coarctation stenting?. (11th December 2013) - Shepherd, Emma; Connolly, Georgia May; Morgan, Gareth
Abstract : The application of coarctation stenting has grown in paediatric and adult practice in recent years. Stent and delivery sheath technology has improved; however, we remain technically limited when implanting small calibre stents through small sheaths in small children, which then have the potential to be dilated to adult size as time passes. We describe the first reported use of the Valeo Biliary Pre-mounted Re-dilatable Stent (Edwards Life Sciences, California, USA) in aortic coarctation with 1 year follow-up including cross-sectional imaging. This 14 kg 3-year-old girl presented following an intracerebral haemorrhage secondary to severe systemic hypertension. Despite implantation through a 7-French sheath, this stent can be postdilated up to 20 mm, and therefore provides an important new addition to the interventional armamentarium.